A Unifying Moving Mesh Method for Curves, Surfaces, and Domains Based on Mesh Equidistribution and Alignment (Communications in Computational Physics, 2025)
A unifying moving mesh method is developed for general $m$-dimensional geometric objects in $d$-dimensions ($d ≥ 1$ and $1 ≤ m ≤ d$) including curves, surfaces, and domains. The method is based on mesh equidistribution and alignment and does not require the availability of an analytical parametric representation of the underlying geometric object. Mathematical characterizations of shape and size of $m$-simplexes and properties of corresponding edge matrices and affine mappings are derived. The equidistribution and alignment conditions are presented in a unifying form for $m$-simplicial meshes. The equation for mesh movement is defined based on the moving mesh PDE approach, and suitable projection of the nodal mesh velocities is employed to ensure the mesh points are not moved out of the underlying geometric object. The analytical expression for the mesh velocities is obtained in a compact matrix form. The nonsingularity of moving meshes is proved. Numerical results for curves $(m=1)$ and surfaces $(m=2)$ in two and three dimensions are presented to demonstrate the ability of the developed method to move mesh points without causing singularity and control their concentration.